APPLICATION OF IMMANUEL KANT'S PHILOSOPHY IN THE THOUGHT OF RELIGIOUS EDUCATION (PHILOSOPHICAL REVIEW OF CRITICISM, RATIONALISM, AND EMPIRICISM) - Muhammad Afthon Ulin Nuha; Muzakki, Hawwin; Musyafa’ah, Nurul (Sunan Kalijaga International Journal on Islamic Educational Research, 2022)
Religious studies are the study of in-depth religion; in its journey, religious studies are divided into two models: dogmatic and empirical. The difference between the two understandings will lead to a reductive understanding of religion in religious studies and can lead to misunderstandings that lead to conflict. To reduce the complex problems of the dichotomy of religious studies, this article tries to draw lessons from Immanuel Kant's criticism; Immanuel Kant's criticism begins by placing doubts on the thinking of rationalists who take a priori knowledge for granted, but on the other hand, Immanuel Kant still keeps trying to investigate how a priori things as science are possible until in the end Immanuel Kant brings up the decision of a priori synthesis as one of knowledge and succeeds in resolving the disagreement between rationalist and empiricist groups. The design of religious studies must start from a doctrinal and empirical dichotomy, then adopt a synthesis of rationalism and empiricism. As Immanuel Kant has said, both a priori and a posteriori thinking, if they stand alone, each has its weaknesses. Likewise, if they stand alone, the dogmatic model of religious studies and the empirical model will end in a reductive understanding.